Septoglomus deserticola emended and new combinations in the emended definition of the family Diversisporaceae - Janusz Błaszkowski; Gerard Chwat (Acta Mycologica, 2013)
An updated morphology of spores of Septoglomus deserticola, an arbuscular mycorrhizal fungus of the phylum Glomeromycota, is presented based on the original description of the species, only one other its definition recently published and spores produced in pot cultures inoculated with the rhizosphere soil and root fragments of an unrecognized grass colonizing maritime sand dunes of the Hicacos Peninsula, Cuba. Phylogenetic analyses of sequences of the large subunit (LSU) nrDNA region of the Cuban fungus confirmed its affinity with S. deserticola deposited in the International Bank for the Glomeromycota (BEG) and indicated that its closest relatives are S. fuscum and S. xanthium. Phylogenetic analyses of sequences of the small subunit (SSU) nrDNA confirmed the Cuban fungus x S. fuscum x S. xanthium relationship revealed in analyses of the LSU sequences and thereby suggested the Cuban Septoglomus is S. deserticola. However, it was impossible to prove directly the identity of the Cuban fungus and S. deserticola from BEG based on SSU sequences due to the lack of S. deserticola SSU sequences in public databases. In addition, phylogenetic analyses of LSU and SSU sequences confirmed the uniqueness of the recently erected genus Corymbiglomus with the type species C. corymbiforme (formerly Glomus corymbiforme) in the family Diversisporaceae and proved that its LSU sequences group in a clade with LSU sequences of G. globiferum and G. tortuosum. Consequently, the two latter species were transferred to Corymbiglomus and named C. globiferum comb. nov. and C. tortuosum comb. nov., and the definitions of the family Diversisporaceae and the genus Diversispora were emended.